A DINÂMICA DE DESENVOLVIMENTO DE PRODUTOS EDUCACIONAIS ELABORADOS POR PEDAGOGOS(AS) NOS MESTRADOS PROFISSIONAIS EM ENSINO DE CIÊNCIAS E MATEMÁTICA DA REGIÃO SUL DO BRASIL - Ortiz, Neiva Lilian Ferreira (2023)
This thesis is part of the research line Teacher Training in Science and Mathematics of the Postgraduate Program in Science and Mathematics Teaching at the Franciscan University and has as its research problem the following question: How do the development dynamics of Educational Products occur? (PE) prepared by pedagogues in the Professional Masters in Science and Mathematics Teaching (MPECM) in the Southern Region of Brazil? In this way, the objective was to analyze the process of the dynamics of development of PE specifically prepared by pedagogues in the MPECM in the Southern Region of Brazil. Aligned with the general objective, the following specific objectives are listed: Understanding the structure and function of MPECM; Map the educational products built by pedagogues in the MPECM in the Southern Region of Brazil; Analyze the potential of PE developed by Pedagogues in an MPECM course in a Postgraduate Program in Science and Mathematics Teaching; Investigate how the concepts of analysis, adherence, innovation and applicability of PE developed by pedagogues in MPECM in the Southern Region of Brazil were implemented; and Identify the dynamics of development of PE developed by pedagogues from the Southern Region of Brazil in Professional Masters in Science and Mathematics Teaching. The methodological approach used was qualitative, bibliographic and documentary, permeated by the content analysis technique (BARDIN, 2016). This is a multipaper thesis, composed of a theoretical framework and four scientific articles, covering the general objective and specific objectives. Of these, two articles were published with partial results and one was accepted. The theoretical bases cover the history of professional master's degrees, the process of constructing EPs, the moment of elaboration of the EP, the moment of qualification and validation of the EP, the moment of socialization of the EP and EP in the teaching of Science and Mathematics. It was found that academic pedagogues from the South Region of Brazil, MPECM, when developing their PE, seek to align their productions with the needs of their professional spaces, meeting the proposal of the Professional Masters (MP) and what they propose. official documents guiding this topic. Thus, in addition to studying and reflecting on the topic, they also brought to these courses professional and academic knowledge of management, public policies, curriculum and teaching-learning processes, among other knowledge from the area of Human Sciences, from which they are graduates, in addition added to the area of Science and Mathematics teaching. Upon concluding this investigation, it appears that the MPECM, in its entirety, contemplate the steps of the EP development dynamics recommended by CAPES, including non-mandatory steps.